Ocean Acidification State in the Highly Eutrophic Tokyo Bay, Japan: Controls on Seasonal and Interannual Variability - Yamamoto-Kawai, Michiyo; Ito, Soichiro; Kurihara, Haruko; Kanda, Jota (Frontiers in Marine Science, 2021)
Seasonal and interannual variabilities in the partial pressure of CO2 (pCO2), pH, and calcium carbonate saturation state (Ω) were investigated in the highly eutrophicated Tokyo Bay, Japan, based on monthly observations that were conducted from 2011 to 2017. There were large variabilities in these parameters for surface and bottom waters due to photosynthesis and respiration, respectively. Warming/cooling and freshwater input also altered the surface Ω. During the observation period, calcium carbonate undersaturation was observed twice in the anoxic bottom waters in summer. The data indicate that anaerobic remineralization under anoxic conditions lowers the Ω, causing undersaturation. These findings suggest that de-eutrophication can decelerate ocean acidification in the bottom waters of Tokyo Bay. However, if atmospheric CO2 exceeds 650 ppm, aragonite undersaturation will be a common feature in the summer bottom water, even if hypoxia/anoxia are alleviated by de-eutrophication.